2019
DOI: 10.1122/1.5066438
|View full text |Cite
|
Sign up to set email alerts
|

Contact tribology also affects the slow flow behavior of granular emulsions

Abstract: Recent work on suspension flows has shown that contact mechanics plays a role in suspension flow dynamics. The contact mechanics between particulate matter in dispersions should depend sensitively on the composition of the dispersed phase: evidently emulsion droplets interact differently with each other than angular sand particles. We therefore ask: what is the role of contact mechanics in dispersed media flow? We focus on slow flows, where contacts are long-lasting and hence contact mechanics effects should b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Hydrogels have become immensely popular in the past decades and these materials have, more recently, been the subject of a broad range of frictional studies. 1,[12][13][14][15] Hydrogels exhibit unique frictional behavior and friction coefficients as low as 0.01 have been reported for hydrogel-on-hydrogel friction (Fig. 1b).…”
Section: Introductionmentioning
confidence: 69%
“…Hydrogels have become immensely popular in the past decades and these materials have, more recently, been the subject of a broad range of frictional studies. 1,[12][13][14][15] Hydrogels exhibit unique frictional behavior and friction coefficients as low as 0.01 have been reported for hydrogel-on-hydrogel friction (Fig. 1b).…”
Section: Introductionmentioning
confidence: 69%
“…This is a simplification compared to real physical suspensions, which may include hydrodynamic forces [48], lubrication forces [49][50][51], and inertial effects [52]. More recently, frictional contact interactions have been proposed to become important when the lubrication layer breaks down upon close contact of particles near jamming, and this has been proposed as a possible mechanism for shear thickening [53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the HB description of structured fluids is not always applicable. Suspensions of soft frictional particles have an effective friction coefficient that can get smaller with rate [64]. Such flow instabilities have been observed in multiple systems [65,66] but were then linked to shear-induced weakening: the shear induces so much fluctuations that the yield stress is affected, even creating an additional critical point [67].…”
Section: Flow Instabilitiesmentioning
confidence: 99%
“…To illustrate the complexity of friction in structured fluids studies, it is helpful to consider that at the same time, numerous simulations have shown that even when one sets the interparticle friction coefficient to zero, the macroscopic friction coefficient of a structured fluid remains finite [91][92][93][94]. Even though numerical simulations of comparable systems have found contradicting relationships between the microscopic and macroscopic friction coefficient [93][94][95], the emergence of a non-zero macroscopic friction coefficient, where microscopically it is negligible, has been been confirmed in experiments [64]. Non-sphericity can further complicate the relation between the microscopic contact laws and the emergent frictional properties [92] but should be less important in slowly sheared emulsions, as the Laplace pressure will keep droplets in emulsions mostly spherical.…”
Section: The Many Faces Of Frictionmentioning
confidence: 99%
See 1 more Smart Citation